2020
DOI: 10.1103/physreve.102.022138
|View full text |Cite
|
Sign up to set email alerts
|

Effective diffusion in one-dimensional rough potential-energy landscapes

Abstract: Diffusion in spatially rough, confining, one-dimensional continuous energy landscapes is treated using Zwanzig's proposal, which is based on the Smoluchowski equation. We show that Zwanzig's conjecture agrees with Brownian dynamics simulations only in the regime of small roughness. Our correction of Zwanzig's framework corroborates well with numerical results. A numerical simulation scheme based on our coarse-grained Langevin dynamics offers significant reductions in computational time. The mean first-passage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Finally, previous work demonstrated that the effects of constant-amplitude roughness upon the mean first-passage time in one dimension can be accounted for easily, provided that there is a separation in length-scales between the roughness and the underlying potential. 32 We believe that this result continues to hold for this two-dimensional, constant-curvature potential. See the supplementary material for details.…”
Section: Illustrative Potentialmentioning
confidence: 58%
See 1 more Smart Citation
“…Finally, previous work demonstrated that the effects of constant-amplitude roughness upon the mean first-passage time in one dimension can be accounted for easily, provided that there is a separation in length-scales between the roughness and the underlying potential. 32 We believe that this result continues to hold for this two-dimensional, constant-curvature potential. See the supplementary material for details.…”
Section: Illustrative Potentialmentioning
confidence: 58%
“…In the supplementary material, we calculated the mean first passage time for a special class of potential where there is a clear separation of length-scales between the (short-scale) roughness of the potential and the underlying potential (long-scale variation). The analysis relies heavily on a recent paper, 32 which is an extension of Zwanzig's work. 36 In this case, the short-scale roughness adds a multiplicative factor that can be accounted for in an elegant manner.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The growth in the order parameters is due to the discovery of the food source by the first ant and the subsequent formation of a pheromone trail. The time at which the order parameter changes nontrivially is commonly known as the first-passage time (FPT), or first hitting time, in stochastic processes [22,79,80], and indicates when a stochastic event occurs for the first time. Due to the random nature of this time, it is more meaningful to look at the mean first-passage time (MFPT) instead, which in our case, is the average time taken for the first ant from the colony to find the food source.…”
Section: Disorder-order Transition In Foraging Antsmentioning
confidence: 99%